Mekanisme Pembiayaan Mitraguna Berkah PNS dengan Akad Murabahah Pada Bank Syariah Indonesia Kcp Tebing Tinggi Sudirman 1 - Fadhillah, Afrahul; Tambunan, Khairina (Medan Resource Center, 2022)
Financing is one of the services of Islamic banks to circulate the budget to other parties, not only banks in accordance with sharia principles. Financing carried out by banks can work together in meeting the wishes of the community. The distribution of the budget in the form of financing is based on the confidence submitted by the budget owner to the budget consumer. One of the consumers of this financing budget is a Civil Servant (PNS) or Prospective Civil Servant (CPNS). The purpose of this analysis is to understand how the Mitraguna Assistance financing system is, after that what provisions must be fulfilled for the application of Mitraguna Blessing financing and also to identify the various problems that are often experienced, and their handling in the Mitraguna Blessing financing mechanism found at Bank Syariah Indonesia Sudirman